Analysis of Adaptation Strategies Among Boarding House Entrepreneurs During COVID-19 - Wulandari, Livia Ayu; Ulya, Laila Listiana (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The COVID-19 pandemic has severely impacted the boarding house business, forcing entrepreneurs to adapt swiftly to maintain their operations amidst financial and occupancy challenges. This situation highlights the difficulties boarding house businesses encounter in ensuring sustainability during uncertain times. This study investigates the adaptation strategies employed by boarding house (kost) businesses during the COVID-19 pandemic. Using a qualitative approach, the research collected data through interviews with four informants, comprising two primary and two secondary sources. The findings emphasize the importance of need-based market segmentation, targeting both students and workers, to maintain occupancy and revenue. Flexible payment schemes, reserve fund management, and cost-saving measures emerged as key strategies to address financial difficulties. Additionally, fostering strong tenant relationships through responsive customer service and empathetic communication enhanced tenant loyalty and ensured long-term occupancy. This study concludes that operational adaptability and effective market segmentation are critical for the survival and growth of rental housing businesses during periods of crisis. These insights provide valuable guidance for similar enterprises navigating uncertain economic conditions while emphasizing the importance of aligning business strategies with tenant needs and maintaining financial resilience.